Effect of methotrexate on intracellular folate pools in purified myeloid precursor cells from normal human bone marrow. - Baram, J; Allegra, C J; Fine, R L; Chabner, B A (The Journal of Clinical Investigation, 1987)
We investigated the effects of the antifolate methotrexate on intracellular folate pools of human myeloid precursor cells (MPCs). Immature MPCs, representing 3.2% of the original marrow population, were selected from normal human bone marrow by immune rosetting. The intracellular folate pools were labeled by incubation with 5 X 10(-8) M [3H]5-formyl-FH4 and were quantitated by high performance liquid chromatography. The predominant folates were 5-methyl-tetrahydrofolate (5-methyl-FH4) (36%), 10-formyl-FH4 (41.4%), 5-formyl-FH4 (12.3%), and FH4 (10.3%). A 12-h exposure to 1 microM methotrexate (MTX) resulted in a 34% reduction in the intracellular concentration of 10-formyl-FH4, a 61% decrease in 5-formyl-FH4, and a 62% decrease in 5-methyl-FH4, as well as the appearance and progressive expansion of the FH2 and 10-formyl-FH2 pools. These changes were maximal after 4 h of incubation with MTX. Paralleling the changes in folates, particularly the increase in FH2, were a 64% reduction in myeloid colony formation and a 77% depression of de novo purine synthesis after 4 h of MTX. We conclude that MTX does not produce quantitative depletion of 10-formyl-FH4 and that its antipurine effect may be mediated by direct inhibition of de novo purine synthesis by FH2 and, at later time points, by MTX polyglutamates.